-6(-3+2)-3u=3(u-1)-1

Add -3 and 2.

-6⋅-1-3u=3(u-1)-1

Multiply -6 by -1.

6-3u=3(u-1)-1

6-3u=3(u-1)-1

Simplify each term.

Apply the distributive property.

6-3u=3u+3⋅-1-1

Multiply 3 by -1.

6-3u=3u-3-1

6-3u=3u-3-1

Subtract 1 from -3.

6-3u=3u-4

6-3u=3u-4

Subtract 3u from both sides of the equation.

6-3u-3u=-4

Subtract 3u from -3u.

6-6u=-4

6-6u=-4

Subtract 6 from both sides of the equation.

-6u=-4-6

Subtract 6 from -4.

-6u=-10

-6u=-10

Divide each term in -6u=-10 by -6.

-6u-6=-10-6

Cancel the common factor of -6.

Cancel the common factor.

-6u-6=-10-6

Divide u by 1.

u=-10-6

u=-10-6

Cancel the common factor of -10 and -6.

Factor -2 out of -10.

u=-2(5)-6

Cancel the common factors.

Factor -2 out of -6.

u=-2⋅5-2⋅3

Cancel the common factor.

u=-2⋅5-2⋅3

Rewrite the expression.

u=53

u=53

u=53

u=53

The result can be shown in multiple forms.

Exact Form:

u=53

Decimal Form:

u=1.6‾

Mixed Number Form:

u=123

Solve for u -6(-3+2)-3u=3(u-1)-1